A comparative study of the impact of interval training and continuous training to complete the 100 meters freestyle swimming - Malek, Ali (Journal of Physical Education, 2008)
The research was conducted to identify the impact of training and continuous training mounted on the delivery of 100 meters freestyle swimming through the application of a training curriculum for a period of 8 weeks by three training modules per week, for a sample of Spahi Iraqi national team for season 2004/2005, who are 8 style, has divided into two Each of the 4 style, as he had been a parity between them in the level of achievement as well as homogeneity, also was aimed at developing curriculum delivery through the use of the training curriculum of twenty-four module mounted on the approved training and the other as the ongoing training, as he had been conducting tests At the end of tribal application platform has been testing Zuhr. The researcher concluded the emergence of moral differences in the results of achievement tests in the two tribal and Zuhr and for the benefit of the tests Zuhr, because of the impact of those methods, which used the latest development in completing sample research, a significant moral difference between the two sets of tests Zuhr officer and pilot in the interest of the pilot group, there is no positive impact by the use of training mounted on the results of the achievements of the same research.